Criação e testagem de banco de espectros de espécies florestais da Amazônia com o uso de dispositivo NIR portátil - FERNANDES, Maysa Lopes (Universidade Federal do Oeste do Pará, 2024)
Forest botanical identification becomes more complex when only the wood is available to define the species, as this subjective and difficult process requires a more in-depth analysis of its characteristics by specialists, who are increasingly scarce and not always available depending on the situation, where the result can take weeks to be issued. The aim of this work is therefore to use infrared spectroscopy in an automatic identification process as a guarantee of great accuracy and speed in recognizing wood species. A portable spectrometer will be used to capture infrared spectra (NIR - Near Infrared Reflectance), with reflectance values within 740-1070 nm from a sample of 10 Amazonian species with 100 specimens of dry wood from various sources at 12% humidity each. The spectrum will be collected in two cutting planes with 2000 repetitions per species, resulting in 20,000 spectra in the database. The project began with the collection of spectra, setting up an extensive database, followed by the verification phase, testing and resulting in instruments for the creation of an automatic recognition system. The species were selected according to the criteria of local commercial importance and defined by commercial groups. It was found that of the 10 species collected there were some correct identifications in the species called Jatobá, which validates the importance of developing this project. These collections will serve as a local collection and, with the creation of a model for identifying each species according to its characteristics informed by the spectra, it will be possible to develop a technology for automatic forest identification.